MEASUREMENT PERFORMANCE OF THE ORGANIZATION AS CONTROL SYSTEM MANAGEMENT ACCOUNTANT - Valdivia Ramos, Román Arturo (2011)
Given the environment of the New Economy transactions and traditional accounting measures to account for these, by themselves, are not sufficient to represent the value of companies under current economic conditions. Often creates value even if it did not happen even any unusual transactions that are posted in business, sometimes enough expectations of future actions for the market value of the business is affected. Thus, more and more companies experience a difference between the results obtained using the approach of creating value and those obtained with the accounting approach of profitability and revenue generation, through a performance measurement system. We try to measure the performance of a company, or area management through measures not - financial, give us an indication (indicator) of the behavior (performance) of an organic unity in a given period. Of course, this model or method of measurement is not unique, there are many and varied, the important thing is to choose the appropriate to the requirements and needs of the company or institution. We believe that the services (or intangibles) are the most important thing in any company or organization and therefore must be measured and then be counted. This is the challenge faced by accountants in the near future